2011
DOI: 10.1109/led.2011.2160612
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Solution Processing of AlInZnO/InZnO Dual-Channel Thin-Film Transistors

Abstract: In this letter, we proposed solution-processed AlInZnO (AIZO)/InZnO (IZO) dual-channel thin-film transistors to realize both proper switching behavior and competitive device performance at the low annealing temperature of 350 • C. A thin IZO layer provides a higher carrier concentration, thereby maximizing the charge accumulation and yielding high saturation mobility μ sat , whereas a thick AIZO layer controls the charge conductance resulting in suitable threshold voltage V th . We therefore obtain excellent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 13 publications
1
53
0
Order By: Relevance
“…In previous studies, InZnO [10,11], ZnSnO [12], InGaZnO [13,14] and Mg-InO [15] have been evaluated for the chemical compound modulation of oxide thin films. Among the numerous materials for chemical composition, aluminum has potential as a carrier suppressor because of its low standard electrode potential (SEP), which is a parameter for oxidation, and abundance in the Earth, which will reduce the cost of the resulting TFTs [16].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, InZnO [10,11], ZnSnO [12], InGaZnO [13,14] and Mg-InO [15] have been evaluated for the chemical compound modulation of oxide thin films. Among the numerous materials for chemical composition, aluminum has potential as a carrier suppressor because of its low standard electrode potential (SEP), which is a parameter for oxidation, and abundance in the Earth, which will reduce the cost of the resulting TFTs [16].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the spin-coated double-active layer, the same double-active layer revealed an amorphous structure. In general, the processing temperature of the spin-coated double-active layer was the same temperature for each layer [9][10][11]. On the other hand, in the case of In2O3, the crystallinity and charge carriers occurred with increasing processing temperature, losing semiconductivity, and resulting in conductive properties [16,17].…”
Section: Resultsmentioning
confidence: 99%
“…Jeong et al reported double-active layer TFTs using AlInZnO (AIZO)/InZnO (IZO) channel layers by spin coating with a field-effect mobility of 5.62 cm 2 /V s at 350 o C [10]. Kim et al also reported AIZO/IZO in the DAL structure for TFTs by spin coating with a field-effect mobility of 1.57 cm 2 /V s at 350 o C [11]. Recently, the chemical stability of a solution-processed double-active layer ZTO/IGZO TFT with a mobility of 1.97 cm 2 /V s at 450 o C were reported [12].…”
Section: Introductionmentioning
confidence: 99%
“…The higher off-current in the IZO-290UVO 3 TFT, comparing the IZO-700 TFT, which was noted above was considered to attribute to the higher concentration of carriers. 1,26 In conclusion, we have proposed an effective method that uses UV/O 3 -assisted annealing to realize the low-temperature fabrication of solution-processed IZO thin-film transistors. Under the UV/O 3 -assisted annealing, the TFT with an IZO thin film fabricated at 290…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under mentioning
confidence: 99%